Penerapan Algoritma Cosine Similarity dan Pembobotan TF-IDF System Penerimaan Mahasiswa Baru pada Kampus Swasta - Apriani, Apriani; Zakiyudin, Hizbu; Marzuki, Khairan (Jurnal Bumigora Information Technology (BITe), 2021)
The era of globalization is marked by the development of technology and information, this has an impact on the human need for information. PMB(Reception New Students) is a routine college activity at each opening of new teachings. The implementation of PMB is not without questions that has been asked before. By making use of technology information the an FAQ (Frequently Asked Questions) was born which contain answers of the questions that are often asked by people who are need information. To reduce the question repeatedly, then an FAQ answering system was built by applying TF-IDF (Term Frequency - Inverse Document) and the cosine similarity algorithm. TF-IDFweighting is a method for giving weights the relationship of a word (term) to a document is based on two concepts, namely frequency of occurrence of words in a document and frequency inverse documents containing the word. Meanwhile, cosine similarity is a method used to calculate the level of similarity between two objects. This method calculates the similarity between two pieces the object represented in two vectors using keywords of a document as a measure. This study uses 7 data samples from all FAQ data obtained from an interview with Ms. Susilawati, S.Kom. The sample data used will go through a processpreprocessing, TF-IDF weighting, and the cosine similarity method fordetermines the highest level of similarity that will come out as a result end. By using TF-IDF weighting and the cosine similarity method on 7 sample data can get an accuracy rate of up to 64,28%.